2019
DOI: 10.1002/mp.13542
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiation‐induced charge imbalance on the dose‐response of a commercial synthetic diamond detector in small field dosimetry

Abstract: Purpose Discrepancy between experimental and Monte Carlo simulated dose–response of the microDiamond (mD) detector (type 60019, PTW Freiburg, Germany) at small field sizes has been reported. In this work, the radiation‐induced charge imbalance in the structural components of the detector has been investigated as the possible cause of this discrepancy. Materials and methods Output ratio (OR) measurements have been performed using standard and modified versions of the mD detector at nominal field sizes from 6 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…As shown in previous studies, the factors k / k vol of the silicon diode detectors are dominated by the density effect with values less than unity, while the microSilicon exhibits less density perturbation mainly owed to the reduced density of the epoxy layers. For the microDiamond detector, it has been recently shown that the observed over‐response is partly caused by radiation‐induced charge imbalance in the detector’s components . Nevertheless, this over‐response is largely compensated in small‐fields by the volume‐averaging effect, resulting in overall correction factors, k, similar to that of microSilicon.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in previous studies, the factors k / k vol of the silicon diode detectors are dominated by the density effect with values less than unity, while the microSilicon exhibits less density perturbation mainly owed to the reduced density of the epoxy layers. For the microDiamond detector, it has been recently shown that the observed over‐response is partly caused by radiation‐induced charge imbalance in the detector’s components . Nevertheless, this over‐response is largely compensated in small‐fields by the volume‐averaging effect, resulting in overall correction factors, k, similar to that of microSilicon.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study has demonstrated the significant role of radiation‐induced charge imbalance in the contacts and cable of the microDiamond detector on its dose response in small photon fields. Although the thickness of the active volume plays directly a minor role in dose perturbation effects, this type of field size‐dependent radiation‐induced charge will be collected in addition to the charge released in the detector’s sensitive volume.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has also quantified an additional effect of radiation-induced charge imbalance, in the PTW microDiamond. 23 At field sizes of length <2 cm radiation induced charge in the electrical contact of the PTW microDiamond is reported to result in an overresponse of the device. Despite these limitations for dosimetry applications the microDiamond remains an area of interest for QA with its response having recently been characterized for use in an MRI linac 24 and for the MRI-associated surface dose from electron contamination.…”
Section: Introductionmentioning
confidence: 99%